Long-term modification of gut microbiota by broad-spectrum antibiotics improves stroke outcome in rats. Issue 5 (16th May 2022) - Liu, Chang; Cheng, Xi; Zhong, Shanshan; Liu, Zhouyang; Liu, Fangxi; Lin, Xinyu; Zhao, Yinan; Guan, Meiting; Xiao, Ting; Jolkkonen, Jukka; Wang, Ying; Zhao, Chuansheng
Abstract : Background: The brain-gut axis is a major regulator of the central nervous system. We investigated the effects of treatment with broad-spectrum antibiotics on gut and brain inflammation, infarct size and long-term behavioral outcome after cerebral ischemia in rats. Methods: Rats were treated with broad-spectrum antibiotics (ampicillin, vancomycin, ciprofloxacin, meropenem and metronidazole) for 4 weeks before the endothelin-1 induced ischemia. Treatment continued for 2 weeks until the end of behavioral testing, which included tapered ledged beam-walking, adhesive label test and cylinder test. Gut microbiome, short-chain fatty acids and cytokine levels were measured together with an assessment of infarct size, neuroinflammation and neurogenesis. Results: The results revealed that the antibiotics exerted a clear impact on the gut microbiota. This was associated with a decrease in systemic and brain cytokine levels, infarct size and apoptosis in the perilesional cortex and improved behavioral outcome. Conclusion: Our results highlighted the significant relationship between intestinal microbiota and beneficial neuro-recovery after ischemic stroke.